Studying modified porous medical membranes by atomic force microscopy - O.A. Konovalova; A.R. Khajdarova; R.G. Ibragimov; M.Kh. Salakhov (Учёные записки Казанского университета: Серия Физико-математические науки)
Polymeric membranes used in medicine and biotechnology, for example in hemodialysis and gas separation, and their modification have been studied. The object of the study is polysulfone porous membranes characterized by reproducible physical properties and well-controlled porosity. Modification of the membranes has been performed in a high-frequency electric discharge at low-pressure (18.4 Pa) in Ar and CF4 medium with an operating frequency of 13.56 MHz and a power of 1500 W. The morphology of the surface of porous polysulfone membranes before and after their treatment by low-temperature plasma has been studied by means of atomic-force microscopy. A Solver P47H (NT-MDT) atomic force microscope with NSG20-type cantilevers has been used in contact and semi-contact operating modes. The following differences in the structure and measured and analyzed phenomenological parameters of polysulfone membranes before and after plasma-based modification have been evolved: dependence of the RMS of roughness of the surface, amplitude of the heights, average arithmetic roughness on the scan scale. It has been revealed that the influence of a high-frequency plasma wave on polysulfone membranes smoothes its surface that indicates a decrease of surface porosity of these membranes and explains the decrease of water permeability and the subsequent increase of retention capacity. It has been shown that plasma treatment improves the hydrophilic surface properties of the internal surfaces of hollow fiber polysulfone membranes. Significant changes have been established in adhesion characteristics of a control set surfaces of polysulfone membranes and the modified ones.